Competition performance variables differences in elite and U-21 international men singles table tennis players - Loh, T. C.; Krasilshchikov, O. (Journal of Physical Education and Sport, 2015)
Physiological indicators say a lot about the preparedness and performance of athletes. We considered the basi Table tennis is one of the most popular and common sports in the world, is considered a very complex sport and is still being developed intensively. With most of the research dedicated to the elite players` skills and fitness, youth and junior players are practically left out of attention. The aim of this study was to compare table tennis game structure among world Top Level Elite (TLE) and under 21 years of age international players` (U-21) categories. Video recordings of a total of 28 matches including semi-finals and finals from the Super Series matches were designated for analysis. The game structure variables selected for this study included match duration, game duration, rallies per game, shots per rally, rally length, rest time between rallies, ball in play in seconds, ball in play in percentage and work to rest ratio. Comparison of all variables between two categories was done using the independent sample t-Test. There were statistically significant differences between the categories in game duration, shots per rally, ball in play in seconds, rally length, and rest time between the rallies (p<.05). This information can assist coaches in improving technical and tactical skills of the table tennis players and to effectively assist prospective youth in reaching the top International standard.